Pengaruh Profitabilitas, Kebijakan Utang dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan Real Estate dan Property Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2017-2022 - Evi Magdalena; Hendriyati Haryani (IJAcc, 2024)
This study aims to determine the effect of profitability, debt policy, and dividend policy to the firm value study objects were using finansial reports of real estate and property companies from 2017-2022. Sampling was selected using purposive sampling with the results of 42 companies. This research uses a quantitative approach with data analysis methods used, namely classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that profitability and debt policy have a significant effect on company value. Meanwhile, dividend policy has no effect on company value.